Quality of life in children with bronchial asthma in Institut Pediatrik Hospital Kuala Lumpur (IPHKL) - Hamdan, Mohamad Azlan (2017)
Background: Asthma is a public health problem that adversely affects different aspects of quality of life (QoL). Childhood asthma is a common chronic disease affecting children worldwide. Objective: To measure the quality of life in children with bronchial asthma who were admitted to the ward due to asthma exacerbation and those who attended general paediatric clinic for follow up in Institut Pediatrik Hospital Kuala Lumpur. Methods: In this cross-sectional observational study, 105 children with physician diagnosed bronchial asthma (57 children attended clinic for follow up and 48 children admitted for asthma exacerbation) were evaluated to measure quality of life and were administered paediatric asthma quality of life questionnaire (PAQLQ). Results: There were 75 boys and 30 girls, age ranged between 7 to 12 years with mean of 8.9 ± 1.5 years. For asthmatic children that were admitted to the ward for exacerbation, the mean age was 8.4 ± 1.2 years and for the asthmatic children who attended the clinic for follow up, the mean age was 9.4 ± 1.6 years. Asthmatic children that were admitted to the ward for exacerbation had moderate impairment in their quality of life as the overall mean score was only 4.0 ± 0.6. The mean score of the quality of life in the symptoms, emotionalfunction and activity limitation domains were 3.7 ± 0.7, 4.4 ± 0.8 and 4.0 ± 0.8 respectively. Children with bronchial asthma who attended the general clinic for follow up had better overall mean score in their quality of life which was 5.9 ± 1.1. This showed that they only had minimal impairment in their quality of life. Meanwhile, the mean score of the quality of life in the symptoms, emotional function and activity limitation domains were 5.8 ± 1.2, 6.0 ± 1.0 and 5.8 ± 1.2. There was no difference of the quality of life score among children with bronchial asthma that had the disease less than 3 years duration and for 3 years and more for the both groups of these asthmatic children. Similarly, there was no difference of the quality of life score among asthmatic children who has normal BMI with asthmatic children who were overweight to obese. Conclusion: Childhood asthma had significant adverse effects on the quality of life of the affected children particularly among asthmatic children that were admitted for acute exacerbation.